Impact of Peganin Alkaloids from Harmala Plant as Inhibitor for Hyaluronidase Enzyme Produced by Staphylococcus Bacteria - Fayyad, Sara; Majeed, Majid (Iraqi Journal of Science, 2025)
Hyaluronidase is an enzyme that primarily breaks down hyaluronic acid, thereby disrupting the structural integrity of the extracellular matrix (ECM) found in connective tissues, which is considered a virulence factor. Peganum is a genus of plants in the family Nitrariaceae that contains a number of alkaloids, including harmaline and harmine, which have been used in traditional medicine. This study aimed to investigate the effect of a plant-active compound (peganin) isolated from a plant sample as an inhibitor of hyaluronidase. In total, 120 samples were randomly isolated from infected burns. Isolates with highly hydrolyzed zones were identified. The Turbidity Reduction Assay was used to assess cell growth and hyaluronidase activity spectrophotometrically. The results showed that (100) out of 120 clinical samples grew bacteria when cultured on a blood agar medium. Also, it was discovered that, out of the 100 isolates, 56 (56%) belonged to S. aureus and had an inhibitory zone of Hyaluronidase range of 5-26mm; the inhibitory zone was increasing over time.